Morphological consequences of interchange reactions during solid state copolymerization in poly(ethylene terephthalate) and polycarbonate oligomers - Gowd, EB; Ramesh, C (Polymer, 2005)
Poly(ethylene terephthalate) (PET) (IV:0.15dL/g) oligomer was obtained by depolymerisation of high molecular weight PET. Polycarbonate (PC) oligomer (IV: 0. 15 dL/g) was synthesized by standard melt polymerization procedure using bisphenol A and diphenyl carbonate in the presence of a basic catalyst. Blends of varying compositions were prepared by melt blending the chemically distinct PET and PC oligomers. The copolymer, poly(ethylene terephthalate-co-bisphenol A carbonate) was synthesized by simultaneous solid state polymerization and ester-carbonate interchange reaction between the oligomers of PET and PC. The reaction was carried out under reduced pressure at temperatures below the melting temperature of the blend samples. DSC and WAXS techniques characterized the structure and morphology of the blends, while (NMR)-N-1 spectroscopy was used to monitor the progress of interchange reactions between the oligomers. The studies have indicated the amorphisation of the PET and PC crystalline phases in solid state with the progress of solid-state polymerization and interchange reaction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: amorphization; poly(ethylene terephthalate); Polycarbonate